Antibacterial activity of reduced graphene-silver oxide nanocomposite against gram-negative bacteria - Rashi Chaudhary; N.B. Singh; Garima Nagpal; Fredrick K. Saah (The Microbe)
The emergence of antibiotic-resistant Gram-negative bacteria necessitates the development of novel antibacterial agents. This study investigates the antibacterial activity of a reduced graphene oxide-silver (rGO-Ag) nanocomposite against Gram-negative bacterial strains, including Escherichia coli and Pseudomonas aeruginosa. The rGO-Ag nanocomposite was synthesized via a chemical reduction method, ensuring uniform dispersion of silver nanoparticles (AgNPs) on the reduced graphene oxide (rGO) sheets. Characterization techniques such as transmission electron microscopy (TEM), X-ray diffraction (XRD), and UV-Vis spectroscopy confirmed the successful reduction and functionalization of GO with AgNPs. The antibacterial activity was evaluated using the disk diffusion method and minimum inhibitory concentration (MIC) assays. Results showed that the rGO-Ag nanocomposite exhibited significantly enhanced antibacterial activity compared to pure AgNPs and rGO. The synergistic effect of AgNPs and rGO led to increased bacterial membrane disruption and reactive oxygen species (ROS) generation, contributing to higher antibacterial efficacy. Furthermore, the rGO matrix prevented the agglomeration of AgNPs, ensuring a sustained and controlled release of silver ions, which prolonged the antibacterial effect. The study highlights the potential of rGO-Ag nanocomposites as effective antibacterial agents against Gram-negative bacteria, offering a promising alternative to conventional antibiotics. The reduced agglomeration of silver nanoparticles in the composite also led to a more sustained release of antibacterial silver ions. Overall, the rGO-Ag nanocomposite shows great potential as an antibacterial agent against Gram-negative bacteria. The findings demonstrate that the antibacterial activities of Pseudomonas sp., and E. coli were improved by graphene-based nanomaterials, which may be used for various biomedical techniques.